Defect type, localization and marker gene expression determines early adverse events of matrix-associated autologous chondrocyte implantation. (October 2015) - Angele, Peter; Fritz, Juergen; Albrecht, Dirk; Koh, Jason; Zellner, Johannes
Abstract: Introduction: Since the first description of autologous chondrocyte implantation (ACI) in 1994 different methods and improvements were established for this regenerative treatment option of large chondral defects. This study analyzes safety and short-term clinical results from characterized ACI using a collagen based biphasic scaffold and evaluates prognostic factors. Methods: 433 patients with a mean age of 33.4 years and localized grade III to IV cartilage defects (ICRS classification) in the knee or ankle were included. Mean defect size was 5.9 cm 2 . Prior seeding of the scaffold, expanded chondrocytes were characterized by RT-PCR on 6 different marker genes (type I and II collagen, aggrecan, interleukin-1 β (IL-1β), vascular endothelial growth factor receptor 1 (FLT-1) and bone sialoprotein-2 (BSP-2)). Clinical outcome was evaluated using a questionnaire for defect history, basic demographics, time elapsed from surgery, 10-point outcome assessments of pain, function and swelling. Moreover, adverse events (AEs) or subsequent treatments were recorded and analysed. Results: Patients improved significantly over baseline (p < 0.0001) in pain, function and swelling. Subjects with later than 12 months follow-up reported nominally greater mean changes. Graft failure incidence was 6% for patients with greater than one year follow-up. Graft-related complications were significantly higher for patellar (p < 0.0001) and degenerative defects (p = 0.005). Elevated expression of FLT-1 (p = 0.02) or IL-1 β mRNA (p = 0.03) was associated with graft-related AEs. A bor derline association was found for low collagen type II expression (p = 0.08). Conclusion: Early graft-related AEs after ACI with a biphasic collagen scaffold are related to defect type, location and marker gene expression. The levels of significance observed for gene expression with respect to graft-related AEs were subordinate to those identified in the analysis of lesion history and location.